Authorities of The Corruption Eradication Commission to Make Demands On Money Laundering Actions. (Study at the Corruption Eradication Commission and Central Jakarta Corruption Court). - Ilham Arfian (Faculty of Law, Merdeka University Surabaya, 2018)
In this thesis, writer raised the theme based on many of the Crime of Money Laudering which often occurred in Indonesia but there is no regulation that regulated clearly about the Authority of Corruption Eradication Commission to prosecution the Crime of Money Laundering. The writer of this thesis using method of sociological approach and type or research is empirical judicial. Legal materials primer analyzed using analysis technique descriptive and secondary legal material using a technique content analysis. As a population that are Corruption Eradication Commission staff and Corruption Crimes Court. Technique arranging primary data is interview and the secondary data using documentary and inventory. From the result with that method, writer receive the answer from the issue which based on Act of Corruption Eradication Commission has right to conducting the prosecution on Crime of Money Laundering because the predicate crime from money laundering is a corruption and based on Act of Crime of Money Laundering not mention or regulate about the authority of prosecution on Money Laundering but based on Criminal Court terms said that simple, fast and cheap court so Corruption Eradication Commission may be conducting about prosecution.